PERCUTANEOUS ENDOSCOPIC GASTROSTOMY FOR LONG-TERM ARTIFICIAL ENTERAL NUTRITION OF SERIOUSLY ILL AND TRAUMA PATIENTS - E. Yu. Strukov; V. L. Belevich; A. V. Shchegolev; Al. A. Kurygin (Вестник хирургии имени И.И. Грекова)
Percutaneous endoscopic gastrostomy was performed on 55 patients of anaesthesiology resuscitation clinic of Military Medical Academy during the last 5 years. A surgery duration was about 13,7±0,5 minutes. The following complications were observed: postoperative wound infections (3 cases), uncontrolled removals of the feeding tube (2 cases), bleeding was noted in 1 patient. The authors recommend the method of percutaneous endoscopic gastrostomy for widespread adoption in patient care institutions according to their experience. The enteral feeding could be used when patients would have the swallowing malfunction during more than 3 weeks.